2015
DOI: 10.1039/c4tb02030h
|View full text |Cite
|
Sign up to set email alerts
|

Water-compatible surface-imprinted microspheres for high adsorption and selective recognition of peptide drug from aqueous media

Abstract: Through employing a synergetic effect of directional and non-directional interactions, surface-imprinted microspheres can selectively recognize thymopentin in aqueous media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Thus, electrostatic interactions play a leading role in the adsorption of the template in NIPs. Using [Bvim][Phe] as an ion‐pair dummy template for preparing MIPs, the charged imidazolium was located inside the imprinted cavities, which would be lead to multiple interactions with l‐ Phe . Hence, salt concentration marginally affects adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, electrostatic interactions play a leading role in the adsorption of the template in NIPs. Using [Bvim][Phe] as an ion‐pair dummy template for preparing MIPs, the charged imidazolium was located inside the imprinted cavities, which would be lead to multiple interactions with l‐ Phe . Hence, salt concentration marginally affects adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…However, multiple interactions commonly exist due to the diversity of biomacromolecules and carriers, including ion-ion electrostatic interactions (20-80 kcal mol À1 ), coordination bonding (20-50 kcal mol À1 ), hydrogen bonding (1-30 kcal mol À1 ), p-p stacking (0-12 kcal mol À1 ), and van der Waals interactions. 30,46 Combined with the above analysis, it could be conrmed that the adsorption of SiO 2 @IL was driven by the synergistic interactions of electrostatic interaction, hydrogen bonding and p-p stacking. The differences between these non-covalent interactions were the probability and binding strength, which obey the Boltzmann distribution.…”
Section: Effect Of Ph On Immobilization Capacitymentioning
confidence: 88%
“…This binding energy of Cl 2p 3/2 showed that it was solely associated with Cl À which was in good agreement with the reference. 30 According to analysis of the XPS results, it was conrmed that the ionic liquid functionalization of SiO 2 @IL had been carried out successfully.…”
Section: Ionic Liquid Functionalization Of Sio 2 Nanoparticlesmentioning
confidence: 99%
“…Microspheres have diverse merits including wide distribution of particle size ranging from several nano‐ to micro‐meters, changeable appearances of solid‐, hollow‐, dumbbell‐, and onion‐like structures, good dispersibility in different solvents, facile preparation approaches, and so on. Depending on the different characters of selected substrates, organic as well as inorganic microspheres both have potentials to allow an imprinting shell generated on their external surface …”
Section: The Currently Popular Imprinting Materialsmentioning
confidence: 99%